An Analysis of Textbook “English in Mind: Student’s Book Starter” for The 7th Year Students of Junior High School Based on Merdeka Curriculum - Encik Siti Adilah; H. Lalu Nurtaat; Kurniawan Apgrianto; Henny Soepriyanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study deals with analysis of textbook for the 7th year students of junior high school based on the latest curriculum, namely the Merdeka curriculum. The purpose of this study was to identify the material presented in the textbook as compatible for grade 7 junior high school. This study was a qualitative descriptive study. The method of this study was content analysis. The data source for this research is the English textbook